The trees around the temples in the Wzniesienia Łódzkie Landscape Park - Świć, Adam (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2002)
The investigations have been carried out on the squares around the temples, whichare localized within the Wzniesienia Łódzkie Landscape Park. There are seven RomanCatholic and four Mariavite churches. The research involves tree stands near the churchesespecially their species and ages structure. This preferences in the plant of the trees wasdetermined and the tree stands around the Roman Catholic and Mariavite churches wascompared.